Representações e desdobramentos da caridade da Igreja Universal do Reino de Deus - Nina Gabriela Moreira Braga Rosas (2010)
The social work that is made by the church Universal of the Kingdom of the God contradicts the common expectation that their mass evangelism would substantially reduce the exercise of charity or make the social action eminently proselytizing. Different types of actions to helping others grow in UCKG according to their particular faith. Temporary models make up a sort of repertoire of social actions, which predominates political figures spearheading assistance actions. The charity of the Universal Church at Minas Gerais, however, is characterized as a welfare practice restricted to institution members, which offers courses of English, write and read, computing, and hairdressing, beyond social routing, legal support and health care. Its peculiarity consists in require a "certificate of probity" to enter and remain in situations of all aid. Another distinguishing of this assistance is that it extends the language and the dynamics of the "war" to the realm of charity, devising a mechanism of competition between workers, volunteers and evangelists who, immersed in the reality of spiritual warfare and in search of recognition, space and status, struggle with God and with each other, to ensure prestige and transit in the rigid hierarchical structure of Universal. These charitable practices reconcile the concepts of poverty with Health and Wealth gospel, reinforcing the faith in a God that restorer goods and blesses their children when they donate to him what they have.